2020
DOI: 10.5144/0256-4947.2020.462
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic dosing of low-molecular-weight heparin may decrease mortality in patients with severe COVID-19 infection

Abstract: BACKGROUND: Venous thromboembolism or extensive thrombosis is relatively common in patients with severe COVID-19 infection and has been associated with increased mortality. During the current COVID-19 pandemic, several prophylactic doses and types of low-molecular-weight heparin (LMWH) are being used worldwide; however, there are no high-quality studies or recommendations for an optimal prophylactic LMWH dose. OBJECTIVES: Investigate the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 23 publications
0
34
0
4
Order By: Relevance
“…Four studies were from China, 20,21,42,47 14 from Europe, 22,23,28,29,31,32,34,35,40,41,43,44,46,48 and 11 from United States (►Table 1). [24][25][26][27]30,33,[36][37][38][39]45 All were retrospective observational studies.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies were from China, 20,21,42,47 14 from Europe, 22,23,28,29,31,32,34,35,40,41,43,44,46,48 and 11 from United States (►Table 1). [24][25][26][27]30,33,[36][37][38][39]45 All were retrospective observational studies.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…29 Eighteen studies reported data exclusively for heparin (UFH or LMWH) treatment. [20][21][22][23]28,[30][31][32]34,35,[40][41][42][43][44][46][47][48] Six studies investigated the role of any anticoagulant treatment, including LMWH or UFH, direct thrombin inhibitors, and/or direct oral anticoagulants. 24,33,[36][37][38]45 Only one study investigated three types of anticoagulant drugs separately (i.e., apixaban, enoxaparin, UFH).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations